Electrically tunable dielectric materials and strategies to improve their performances - Kong, Ling Bing (2012)
Electrically tunable dielectric materials have potential applications as various microwave devices, such as tunable oscillators, phase shifters and varactors High dielectric tunability, low dielectric loss tangent and appropriate level of dielectric constant, are basic requirements for such applications. Ferroelectric materials are the most promising candidates. In general, strontium titanate (SrTiO(3) or ST) is used for devices operating at low temperatures, while the devices based on barium strontium titanate (Ba(1-x)Sr(x)TiO(3) or BST) are operated at room temperatures The modifications of parent ferroelectrics, such as Sr(1-x)Pb(x)TiO(3), BaZr(x)Ti(1-x)O(3) and BaTi(1-x)Sn(x)O(3) etc. have also been widely investigated. In addition, there have been reports on electrically tunable dielectric materials, based on non-ferroelectric compounds, such as microwave dielectrics and carbon nanotube (CNT) composites. Specifically for ferroelectric materials, a critical issue is the reduction of the dielectric losses, because their dielectric loss tangents are relatively high for practical device applications Recently, many efforts have been made in order to reduce the dielectric losses of BST based ferroelectrics. An efficient way is to dope oxides that have low dielectric losses, such as MgO, ZrO(2) and Al(2)O(3), TiO(2), LaAlO(3), and Bi(1 5)ZnNb(1 5)O(7) etc. into the ferroelectric materials. In addition to the reduction in dielectric loss tangents, the introduction of oxides would also be able to modify the dielectric constant to be suitable for practical design of various devices Meanwhile, dielectric and electrical properties of thin films can be improved by chemical doping, substrate adaptation, orientation and anisotropy optimization This review provides an overall summary on the recent progress in developing electrically tunable dielectric materials, based on ferroelectrics and non-ferroelectrics, with a specific attention to the strategies employed to improve the performances of ferroelectric materials for microwave device applications.